AKT1 as a therapeutic target for platinum-resistant SOX2 positive ovarian cancer cells - Mengyang Xue; Li Kang; Yunfeng Zhang; Xixia Yuan; Jiwen Li; Rong Zhang; Jiemin Wong (Scientific Reports)
Abstract Ovarian cancer remains the most lethal gynecological malignancy, largely owing to its chemotherapy resistance and high recurrence rate. Emerging evidence has linked the aberrant expression of SOX2, a transcription factor that is important in the development and maintenance of stem cell state, with chemoresistance and poor prognosis of ovarian cancer patients. In this study, we aimed to elucidate the mechanisms that drive aberrant SOX2 expression in ovarian cancer cells. By examining multiple ovarian cancer cell lines and a panel of clinical tumor samples, we observed a broad overexpression of SOX2 in ovarian cancer cell lines and tumors. To identify signaling pathway(s) that drives SOX2 overexpression in ovarian cancer cells, we screened a set of small-molecule kinase inhibitors that target 30 major cellular kinases. Among the top hits identified are AKT inhibitors. We demonstrated that inhibition or knockdown of AKT1 can drastically downregulate SOX2 protein level, impairs the growth and stemness of SOX2-positive ovarian cancer cells, and markedly sensitize SOX2-positive ovarian cancer cells to platinum drugs. Mechanically, we found that AKT1 drives SOX2 overexpression primarily by enhancing its protein stability and does so by phosphorylating SOX2 at threonine 116. Altogether, our study reveals an underlying mechanism that drives SOX2 overexpression in ovarian cancer and underscores pharmacological inhibition of AKT1 as a potential therapeutic strategy to sensitize SOX2-positive ovarian cancer to platinum drugs.